STRATEGI KOMUNIKASI PEMASARAN RUMAH ATSIRI INDONESIA DALAM MENINGKATKAN JUMLAH PENGUNJUNG (The Commercium, 2023)
This study aims to find out how the application of the Indonesian Essential House Marketing Communication Strategy in Increasing the Number of Visitors. This research is a qualitative descriptive research with a case study method. The paradigm used is the constructivism paradigm in which social processes are obtained through actions and interactions created by individuals continuously so as to produce a reality that is owned and experienced individually. Data collection was obtained through observation and in-depth interviews. The results of this study indicate that the promotion strategy used by Rumah Essential Indonesia is by utilizing marketing communications with the concept of an integrated marketing communication strategy and promotion through social media. Social media plays an important role in promoting services at Rumah Atsiri Indonesia